SILEK LANYAH: PERKEMBANGAN DARI TRADISI KE KREASI DI DESA KUBU GADANG KELURAHAN EKOR LUBUK KECAMATAN PADANG PANJANG TIMUR KOTA PADANG PANJANG - Khairah, Wardhatul; Desfiarni, Desfiarni; Mansyur, Herlinda (SENDRATASIK UNP, 2019)
The purpose of this study is to describe and analyze the development of Silek Lanyah from tradition to creation in Kubu Gadang Village, Ekor Lubuk Village, Padang Panjang Timur District, Padang Panjang. The type of study was a qualitative with descriptive methods. The instrument of study was the researcher and it was assisted by supporting instruments such as stationery, camera and gadget / smartphone. The type of data used primary and secondary data. Techniques of data collection carried out by doing literature study, observation, interview and documentation. Techniques of data analysis were done by doing collection, reduction,Â  data presentation and making conclusions. The result shows that Silek Lanyah has progressed in terms of the quality of the movements, performers, costumes, music and practice camp or targets. The development of Lanyah Silek originates from Silek Tuo Gunuang as a source of Silek Lanyah movement. Young men and women in Kubu Gadang Village as the perpetrators of Silek Tuo Gunuang preserve their traditional arts that are developed in a new form, which become a martial arts attraction as a icon of touristm.Keywords: silek lanyah, the development, tradition to creation